Say what? (xiao) - Bennett, Gregory A. (Linguistica (Ljubljana), 2012)
In this paper, I compare two variants for representing laughter in synchronous Japanese Twitter discourse: (xiao), the kanji symbol meaning "laughter "situated between two parentheses, and w, the first letter of the romaji transliteration of that same word wara. I argue that they are digital equivalents of what Gumperz (1982) calls contextualization cues and that users employ each variant to convey a pragmatic tone, or what Goffman (1981) refers to as linguistic keys. To demonstrate, I analyze the public Tweets of saywhat327, a male Japanese university student. I find that saywhat327 (1) uses (xiao) to key his utterances as warm/friendly in the formal register of Japanese, (2) uses w to key his utterances as playful in the informal register of Japanese, and (3) uses both variants with informal Japanese to key two separate utterances within the same Tweet as warm/friendly and playful, respectively, based on the semantic content of each utterance. In each of these cases, I argue that @saywhat327 builds rapport with his interlocutor by keying his utterances via the (xiao) and w cues.
Keywords: analiza diskurza; analyse du discours; discours électronique médié; elektronski diskurz; Japanese; japonais; japonščina; rire; sociolinguistics; sociolinguistique interactionnelle; sociolingvistika; spletni diskurz